Verbal Rhetoric Skills in Bahmayari’s Storybooks and Mazandaran’s Proverbs - Ali Razzaghi Shani; Ahmad Ghanipour Malekshah; Morteza Mohseni; masoud ruhani (مطالعات زبانی و بلاغی)
The subject of this article is Verbal Rhetoric Skills in Bahmayari’s Storybooks and Mazandaran’s Proverbs. Proverbs is one of the branches of folk literature. Although it seems that proverbs are apparently far from the aesthetic assets, less proverbial examples can be found without any rhetoric skills. One of the important factors that bring beauty and efficiency is verbal rhetoric arrays. In this textbook, novel verbal skills in 6023 proverbs of Bahmanyari's storybooks and 2023 Mazandaran's proverbs from its culture by Mostafa Ansari was investigated and analyzed with comparison and description method, and also content analysis according to the library resources. This result is obtained that, employing novel verbal skills have great influence on the rhetoric and effectiveness of the Mazandaranis' proverbs and storybooks which has caused its reputation and popularity. Beyond the total novel verbal skills, the repetition and commitment have the highest frequency and chiasmus has the lowest frequency in rhetorical of proverbs. The number of arrays used in storybooks proverbs are more than Mazandaran's proverbs. The variety of arrays in Mazandaran's proverbs are less and the arrays that were used in them are more simple and sensible: this suggests that speakers of Persian proverbs have more knowledge of literary than the speakers of Mazandarani' proverbs. Of course, the poem form of storybooks proverbs has some impact in this regard.